A reassessment of Eugenia astringens (Myrtaceae) and its synonyms, including their formal typification - Delprete, Piero G. (Phytotaxa, 2020)
Giovanni Casaretto published Eugenia rotundifolia Casaretto (1842: 40) using material that he collected in Restinga vegetation between Copacabana and Lagoa Rodrigo de Freitas, Rio de Janeiro, Brazil. Berg (1857: 287) treated E. rotundifolia Casaretto as a distinct species, and recognized two varieties. However, the binomial E. rotundifolia (Walker-Arnott 1836: 335) Wight (1841: 17) was previously published for a taxon occurring in Sri Lanka. Therefore, Casaretto’s name is a later superfluous homonym and illegitimate. In a recent article on the typification of plant names published by Casaretto, Delprete et al. (2019) proposed E. casarettoana Delprete (2019: 25) as a substitute name for E. rotundifolia Casaretto. However, Delprete and his collaborators overlooked that the name E. casarettoana O. Berg (1857: 520) was previously published using material collected by Martius near the town of Coari, state of Amazonas, Brazil, and belongs to a distinct species occurring in the Brazilian Amazon. Also, Berg (1857) spelled the specific epithet “casaretteana” without explaining to whom he dedicated the epithet. It is obvious that it was dedicated to Casaretto, as no other botanist or plant collector has a similar last name. Therefore, according to Recommendation 60C of the ICN (Turland et al. 2018), the spelling of this epithet should be corrected to casarettoana, as it has been done for this and other specific epithets dedicated to Casaretto (Delprete 2016).